Negotiating strategically : one versus all - Nikolopoulos, Andreas, 1949- (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2011)
'Negotiation is a key part of daily lives, but learning how to negotiate successfully is a valuable skill. The author provides a tool kit for negotiation, demonstrating new methods and giving practical advice'--
Includes index.
Keywords: Negotiation in business; Negotiation; Conflict management